Impact of Peritoneal Closure on Inguinal Hernia Incidence After Robot-Assisted Radical Prostatectomy - Naoki Imasato; Shugo Yajima; Ryo Andy Ogasawara; Minoru Inoue; Kohei Hirose; Ken Sekiya; Madoka Kataoka; Yasukazu Nakanishi; Hitoshi Masuda (Surgical Techniques Development)
Background/Objectives: Inguinal hernia (IH) is a common complication after robot-assisted radical prostatectomy (RARP), significantly impacting patients’ quality of life. This study aimed to evaluate whether peritoneal closure reduces the incidence of IH after RARP. Methods: A retrospective analysis was conducted on 772 patients who underwent transperitoneal RARP between April 2018 and March 2023. Patients with a history of IH surgery were excluded. Peritoneal closure, introduced in December 2021, was performed during the final steps of RARP in 144 patients. The incidence of IH was compared between patients with and without peritoneal closure. Multivariate analysis was performed to identify significant predictors of IH. Results: IH occurred in 73 patients (9.5%)—5 (3.5%) in the peritoneal closure group and 68 (10.8%) in the no peritoneal closure group. Multivariate analysis revealed that the absence of peritoneal closure (hazard ratio [HR] = 4.55, p = 0.04) and low body mass index (BMI < 23 kg/m2; HR = 2.51, p = 0.001) were significant predictors of IH. The two-year IH-free survival rate was 96.5% in the peritoneal closure group and 89.2% in the no peritoneal closure group. Conclusions: Peritoneal closure significantly reduces the incidence of IH after RARP. This simple and effective technique may serve as a valuable preventive measure against postoperative IH, potentially improving surgical outcomes and patient quality of life. Further studies are warranted to confirm these results in diverse patient populations.